Creative Business in Australia: Learnings from the Creative Industries Innovation Centre, 2009 to 2015 - Lisa Colley (Editor); Paul Ashton (Editor); Lisa Andersen (Editor) (UTS ePRESS, 2021)
As the largest ever Australian government investment in creative industries development, the Creative Industries Innovation Centre delivered tailored business services to more than 1500 creative businesses from 2009 to 2015 and provided industry intelligence and advice for public policy and peak sectoral activity. This collection gives an overview of the current ‘state of business’ in Australia’s creative industries – both as an industry sector in its own right and as an enabling sector and skills set for other industries – and reflects on business needs, creative industries policy and support services for the sector. With contributions from the Centre’s team of senior business advisers and from leading Australian researchers who worked closely with the Centre –including experts on design-led innovation and the creative economy – and case studies of leading Australia creative businesses, the book is intended as and industry-relevant contribution to business development and public policy. Content links to the publicly accessible Creative Industries Innovation Centre Collection Archive at the UTS Library, which holds material from Centre’s activities over its six years of operation.